Pandangan Ulama Terhadap Image Processing Pada Astrofotografi Di BMKG Untuk Rukyatul Hilal - Riza Afrian Mustaqim (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2018)
BMKG develops rukyatul hilal by using Image processing in astrophotography. The process of image processing on the cresent that can not be ascertained its existence. Image processing is able to clarify the vivid image of the cresent becoming more vivid and invisible. This study examines the views of ulama related to the validity of the use of image processing. There is a difference between the scholars. Firstly, the scholars did not allow the use of image processing because of the use of limited tools to aid vision. Secondly, scholars who allow the use of image processing but only limited to clarify the image of the new moon. Thirdly, scholars who allow the use of image processing as a whole, because the step is a scientific process to ensure moon. Keyword: Image Processing, Rukyatul hilal, Ulama